Probable secondary hemophagocytic lymphohistiocytosis manifesting as central nervous system lesions after COVID-19 vaccination: a case report - Kim, Ju Hye; Chung, Ji Yeon; Bong, Jeong Bin (Frontiers in Neurology, 2024)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a rare systemic inflammatory disease commonly characterized by histiocyte infiltration in multiple organs, such as the liver, spleen, lymph nodes, bone marrow, and central nervous system. The clinical features of HLH include fever, splenomegaly, cytopenia, hypertriglyceridemia, hypofibrinogenemia, and elevated blood ferritin levels. HLH is categorized as either primary or secondary. Coronavirus disease 2019 (COVID-19) vaccines may occasionally trigger secondary HLH, which is related to hyperinflammatory syndrome.A 58-year-old woman, previously diagnosed with Graves' disease, presented with cognitive decline two weeks after receiving the first dose of the ChAdOx1 nCoV-19 vaccine. Brain MRI revealed a hyperintense lesion on T2-weighted and fluid-attenuated inversion recovery images in the bilateral subcortical white matter and right periventricular area. Vaccination-associated acute disseminated encephalomyelitis was suspected and methylprednisolone and intravenous immunoglobulin (IVIg) were administered. From the 5 th day of IVIg administration, the patient developed fever and pancytopenia. In the findings of bone marrow biopsy, hemophagocytosis was not observed; however, six of the eight diagnostic criteria for HLH-2004 were met, raising the possibility of HLH. Although there was no definitive method to confirm causality, considering the temporal sequence, suspicion arose regarding vaccine-induced HLH. Splenectomy was considered for therapeutic and diagnostic purposes; however, the patient died on the 28th day of hospitalization owing to multiple organ failure.To date, 23 cases of COVID-19 vaccine-related HLH have been reported. Additionally, HLH in COVID-19 patients has been reported in various case repots. To the best of our knowledge, this is the first reported case of central nervous system involvement in HLH related to any type of COVID-19 vaccine. This case suggests that even when there are no systemic symptoms after COVID-19 vaccination, HLH should be considered as a differential diagnosis if brain lesions are suggestive of CNS demyelinating disease.